Health practices of children and women with disabilities - Celia M. Reyes; Charina Cecille M. Reyes; Arkin A. Arboneda (Philippine Institute for Development Studies (PIDS), 2017)
Persons with disabilities (PWDs) in the Philippines generally face several difficulties in getting hold of a much needed medical attention, including transportation and other barriers to access, and financial difficulties, among others. This study is an offshoot of the joint project of the Philippine Institute for Development Studies and the Institute of Developing Economies that focuses on the health conditions of PWDs, both adult women and children, in Mandaue City and San Remigio, Cebu, Philippines. Using primary data collected through survey and key informant interviews with various stakeholders, the study highlights the lack of access to appropriate services for PWDs and that out-of-pocket expenditures on health cover a significant portion of their income. Some recommendations include the provision of early detection and intervention, routine monitoring of programs, the expanded utilization of medical and nursing students in the communities in providing preventive care services, the expanded coverage for medications and nursing/caregiver support, and the increased training on health-care providers and personnel, particularly in the communities.
Keywords: 330; Philippines; health; health practices; access to health care; person with disability; PWD; San Remigio; Mandaue City; Cebu